INTELLIGENT AUTOMATED SYSTEM OF CONTROL OF KNOWLEDGE: LINGUISTIC SUBSYSTEM - Katerynchuk, I.C.; Kulyk, B.M.; Komarnytska, O.I. (Journal of Information Technologies in Education (ITE), 2010)
A flowchart linguistic structure (morfological, syntactical, semantic and pragmatic) analysis of sentences of the automated system of control of intellectual knowledge. The model of artificial intelligence recognition and evaluation of textual answers.